Enhancing local revenue with land and construction tax incentives: fair and balanced tax approaches - Kusumastuti, Dora; Musa , Hussein Gibreel (CV. Ius et Ambientis, 2023)
PBB-P2 tax (Land and Building Tax-Rural and Urban) and other valid sources provide local revenue. In article 10 of Regulation of the Minister of Finance of the Republic of Indonesia Number 208/PMK.07/2018 for the Assessment of Rural and Urban Land and Building Taxes,